Full-scale test and numerical modeling on deformation and damage behavior of segmental joints under ultimate compression-bending load. (15th March 2023) - Guo, Wenqi; Feng, Kun; Zhou, Yili; Yang, Wenqian; Lu, Xuanyi; Xiao, Mingqing; He, Chuan
Graphical abstract: Highlights: The mechanical behavior of joint is investigated through test-numerical comparison. The failure mechanism and characteristics of segmental joint are revealed. Deep investigation on the mechanical mechanism and yield judgment of bolt. Abstract: Investigating the deformation and damage behavior of segmental joints is of great significance for design optimization safety evaluation of shield tunnel. In this study, the full-scale tests of segmental joint under compression-bending load were carried out. A three-dimensional numerical calculation model with concrete damaged plasticity (CDP) constitutive was developed, of which the accuracy was validated by the full-scale test. The mechanical behavior and damage evolution process of the segmental joint, the strain of the bolt and the reinforcement are investigated. The experimental and numerical results revealed that the bending moment-rotational angle curves of segmental joint can be divided into four stages under positive bending moment and three stages under negative bending moment. The difference is mainly due to that the waterproof structure is only set outside the segmental joint. The maximum stress of the bolt occurred in the front of the thread rather than the corresponding location of the joint surface. Compared with Von Mises stress criterion, the method of judging the yield of bolt by the ultimate elastic strain usually adopted in the full-scale test is conservative. The bolt yields under negative bending moment later than that under positive bending moment, and the difference is about 49.8%. The maximum strain of the reinforcement is located at the first stirrup near the joint surface. The strain of the reinforcement at the sleeve side is obviously larger than that at the hand hole side under positive bending, while the opposite is true under negative bending.